ANALISIS PENERAPAN METODE PENYUSUTAN AKTIVA TETAP DAN PENGARUHNYA TERHADAP LABA PADA CV. ARAFAT JAYA - ., Rumiatun Wahdaniah (EKONOMIA, 2012)
CV. Arafat Jaya is one company engaged in service and has a profit-seeking entity to provide public transportation services. Allocation of depreciation of fixed assets and services reflect the participation of fixed assets to generate earnings for the company, depreciation is a decrease in the value of the benefits and value of assets owned. The magnitude of this decline should be calculated and allocated as depreciation expense in the end compared to the revenue ina particular accounting period.The analysis method used is the method by comparing the ratio of the straight-line method of depreciation, double declining balance, and sum-year figures.From the analysis and discussion in mind that profit using the straight-line method during the period 31-12-2011 at Rp 3.817.820.490,00, double-declining balance method of Rp 993.028.642,00 and the number of the number of years of Rp 2.598.392.900,00 Acquisition of earnings based on the calculation of straight-line method was higher when compared with the double-declining balance method and the total number of years.